Kajian Penggunaan Obat Nasofaringitis Akut Berdasarkan Indikator Peresepan World Health Organization (WHO) di Puskesmas Antibar Mempawah - Putri, Nabilah Ananda; Susanti, Ressi; Kusharyanti, Indri (Jurnal Farmasi & Sains Indonesia, 2025)
Acute nasopharyngitis is a mild respiratory infection caused by a virus. This disease is common in children to adults. The World Health Organization (WHO) states that more than 50% of drugs are used inappropriately, causing polypharmacy, antibiotic resistance, wasteful costs and drug interactions. This study aims to assess the appropriateness of drug use for acute nasopharyngitis at Antibar Mempawah Community Health Center based on WHO prescribing indicators. This study is a non-experimental study with a descriptive cross sectional design. Data were collected retrospectively through 411 medical records of acute nasopharyngitis patients in 2022 with randomized sampling technique. The results obtained were the average number of drug items per prescription sheet was 3.35, the percentage of drugs prescribed with generic names was 95.13%, prescribing drugs with antibiotics was 42%, prescribing drugs with injection preparations was 0%, drugs prescribed based on the National Formulary was 75.9%.